Long-term fertilisation form, level and duration affect the diversity, structure and functioning of soil microbial communities in the field - van der Bom, Frederik; Nunes, Inês; Raymond, Nelly Sophie; Hansen, Veronika; Bonnichsen, Lise; Magid, Jakob; Nybroe, Ole; Jensen, Lars Stoumann (Soil biology & biochemistry, 2018)
Applications of mineral and organic fertilisers are an important agricultural practice for improving crop yields, but these applications can also affect soil properties, as well as the microbial community structure and function. The objective of this study was to compare the legacy effects of long-term applications of mineral fertiliser versus animal slurry on the composition and activity of soil microbial communities, and to investigate the significance of their application level and change in long-term management. Soils were collected from the Long-Term Nutrient Depletion Trial in Taastrup, Denmark, which consists of seven mineral and animal slurry fertilisation treatments (20 years) plus seven additional treatments that underwent a shift in their long-term management after 14 years. Microbial communities in soils receiving animal slurry had multiple substrate-induced respiration (MSIR) metabolic fingerprints that clearly differentiated them from those in mineral fertiliser-amended soils. The differences in fingerprints were mainly related to soil total C and pH. Bacterial community analysis by 16S rRNA gene amplicon sequencing showed that animal slurry applications increased bacterial community richness and diversity compared with mineral fertiliser applications, and also increased the relative abundance of several copiotrophic taxa. Even high levels of annual nutrient applications (mineral and organic) promoted copiotroph-dominated bacterial communities to the detriment of oligotrophs, with N inputs exerting a greater influence on bacterial community structure than P or K levels. Stable long-term annual fertiliser applications supported a diverse bacterial community, while a change in nutrient management decreased bacterial diversity. This study documents the differing, time-dependent effects of organic inputs and mineral fertilisation on the composition and functionality of the soil microbial community and highlights the importance of nutrient input levels for soil bacterial community structure. •Soils of a Long-Term Nutrient Depletion Trial were amended with mineral fertilizer or animal slurry.•Microbial metabolic fingerprints (Microresp™) differed between mineral and slurry amended soils.•Animal slurry applications enhanced bacterial community richness and diversity.•High levels of nutrient inputs promoted copiotroph-dominated bacterial communities.•Changed long-term management decreased bacterial diversity compared to stable annual applications.